Study of User Experience in Learning Management Systems - Ramírez García, José de Jesús (IE Revista de Investigación Educativa de la REDIECH, 2021)
The use of Learning Management Systems (LMS) has currently become essential in the teaching and learning process; it is important to take into account both usability and user experience in the design of these systems, various authors have focused their efforts to build evaluation guides for both usability and user experience (UX). The goal of this work is to present the opinions of six teachers regarding their satisfaction as users of these systems, along with the results obtained from the application of the User Experience Questionnaire short version (UEQ-S) carried out on 12 students. These results are part of the diagnosis of a research that follows the design-based research methodology. This work has a qualitative approach, documentary analysis techniques, semi-structured interviews and the UEQ-S questionnaire are interpreted. Among the results obtained, it stands out that although the pragmatic part is better evaluated, it is in the hedonic aspects where more attention should be paid. The conclusions found that it is imperative to take into account design factors linked to hedonic and emotional design, to generate better user satisfaction.